RESEARCH ON SOCIAL MEDIA ENGAGEMENT INTO B2B BY VARUN JANGRA MBA2016-17 - JANGRA, VARUN (2017)
The study aims to develop understanding position of social media in business to business (B2B) industry sector. According to some researchers, B2B industry sector has failed to apply social media use into their marketing activities, there are literature which suggest that B2B sector has always fallen behind business to customer (B2C) sector over social media parameters. This research aim to find industry sectors who implement social media for B2B purpose and also, to understand how B2B companies are using social media strategy to engage virtual audience.